2017
DOI: 10.21307/immunohematology-2019-008
|View full text |Cite
|
Sign up to set email alerts
|

The Vel blood group system: a review

Abstract: The blood group antigen Vel has been one of immunohematology's greatest enigmas: the variation in antigen strength from one individual to another, the property of anti-Vel to readily hemolyze Vel+ red blood cells (RBCs), and the difficulty to screen for sufficient numbers of Vel-blood donors had made Vel a tough nut to crack. In 2013, a small, previously unknown protein called small integral membrane protein 1 (SMIM1) was identified on the RBC by three independent research groups using different approaches, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 33 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…SMIM1 was found to be hypermethylated in MUHO. This gene codifies a protein that is involved in red blood cell formation being also an antigen in the Vel blood group (79). This blood group is more prevalent in individuals of Nordic ancestry and, so far, there is no known connection between this protein and dysglycemia.…”
Section: Dna Methylation Signatures In Subjects With Muho Vs Subjects With Mhomentioning
confidence: 99%
“…SMIM1 was found to be hypermethylated in MUHO. This gene codifies a protein that is involved in red blood cell formation being also an antigen in the Vel blood group (79). This blood group is more prevalent in individuals of Nordic ancestry and, so far, there is no known connection between this protein and dysglycemia.…”
Section: Dna Methylation Signatures In Subjects With Muho Vs Subjects With Mhomentioning
confidence: 99%
“…In 2013, an unknown protein called "small integral membrane protein 1" (SMIM1) was identified on the RBC membrane, and it was demonstrated that Vel-red blood cells lacked SMIM1. Clinically, anti-Vel is important, with severe transfusion reactions being described, 2 and there is a very limited number of blood donors, with 20-30 known donors and about 50 cryopreserved packed red blood cells in Germany. 3 This patient had previously been transfused more than 5 years ago and had no history of pregnancy.…”
mentioning
confidence: 99%